2020
DOI: 10.1038/s41591-020-0805-8
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant immunotherapy leads to pathological responses in MMR-proficient and MMR-deficient early-stage colon cancers

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
757
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 957 publications
(791 citation statements)
references
References 63 publications
26
757
1
7
Order By: Relevance
“…(n = 20/20) pathological response in dMMR and a 27% (n = 4/15) pathological response in proficient MMR tumors after 4 weeks of treatment. 39 Although pathological stage is the key determinant of treatment and survival, additional predictive and prognostic markers are crucial. In this context, MSI, KRAS, 18q loss of heterozygosity, and TP53 and BRAF mutations have been studied, but most are not included in the treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…(n = 20/20) pathological response in dMMR and a 27% (n = 4/15) pathological response in proficient MMR tumors after 4 weeks of treatment. 39 Although pathological stage is the key determinant of treatment and survival, additional predictive and prognostic markers are crucial. In this context, MSI, KRAS, 18q loss of heterozygosity, and TP53 and BRAF mutations have been studied, but most are not included in the treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…However, TMB does not capture the full evolutionary history of the tumor and several patients do not respond despite their TMB status. In addition, a recent study has shown that mismatch repair-proficient colorectal cancers can also achieve clinical response 44 . Motivated by this, we propose that immune dN/dS can be used, in addition to TMB and escape mechanisms, to stratify patients into adapted and escaped.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that even mismatch repair proficient tumors display a pathological response 44 , emphasizing the need for quantifying the true immunogenicity of the cancer genome and their potential clinical response to immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, immunotherapy has been a hotspot in the research of major tumor types. In the COAD eld, research on the high-level microsatellite instability(MSI-H) population has been carried out successively since 2015, from Keynote 016, Keynote 164 to Checkmate 142 and NICHE research results all indicate the extraordinary e cacy of immunotherapy [33][34][35][36]. The patients with MSI-H have a better prognosis than those with microsatellite stability(MSS).…”
Section: Discussionmentioning
confidence: 99%